The Existence and Independence of Women in the Novel Isinga by Dorothea Rosa Herliany: A Review of Feminist Literary Criticism - Sumartini, Sumartini; Nuryatin, Agus; Prabaningrum, Dyah; Afriyanti, Rinna; Syavica, Cindy Gea (Formosa Journal of Multidisciplinary Research, 2025)
Literary works are a means for authors to convey thoughts, ideas, ideas and even criticism of phenomena and problems that occur in society. The issue of women in society is one of the exciting topics raised in literature. The novel Isinga presents the issues of Papuan women related to the existence and independence of women and their efforts to realize their existence. This research is qualitative, and the data analysis method is hermeneutic. The consequences of using hermeneutics are bound to two things: first, ascertaining the content in a word, sentence, text, and so on, and second, understanding the forms of instruction contained in the symbols. The research results show that Papuan women have a very high existence as individuals and social beings. Papuan women have an independent attitude formed due to circumstances that force their awareness to maintain their existence. Efforts made by women to realize their existence and foster women's independence include (1) trying to learn new things, (2) opening a business/trading in the market, (3) providing counseling for women and adolescents, (4) providing skills training for women and adolescents.